PENGOLAHAN NUGGET TAHU, MENINGKATKAN KETERAMPILAN IBU MENCEGAH STUNTING PADA BALITA - Siregar, Nova Sontry Node; Simamora, Mayes Felda; Siboro, Kino; Purba, Dewi (Jurnal Masyarakat Indonesia (Jumas), 2025)
Stunting is still a major nutritional problem for babies and children under two years of age in Indonesia. This condition must be immediately eradicated because it will hinder the momentum of Indonesia's golden generation in 2045. The main causes of stunting include inadequate nutrition and nutrition intake for children, wrong parenting patterns due to lack of knowledge and education for pregnant and breastfeeding mothers, poor environmental sanitation. living and limited access to health facilities. An alternative local food processing that can be introduced to the community is tofu nuggets. Tofu can be processed into various shapes and other types of food, one of which is tofu nuggets. The aim of this activity is to improve mothers' skills in processing tofu nuggets to prevent stunting in toddlers. This type of activity is a demonstration of processing tofu nuggets for 30 mothers who have children aged ≤ 2 years in Pasaribu Village. The results show that there are differences in mothers' knowledge and skills before and after practice/demonstration. The results of interviews with participants stated that practice/demonstration was very helpful in conveying information about processing balanced nutrition for toddlers to mothers so that the information could be conveyed more clearly and precisely. Demonstration activities also explain an object that can be given, for example the food consumed contains carbohydrates, protein, minerals and so on. The hope of this research is for mothers who have toddlers to make efforts to prevent stunting (fulfilment of pregnancy nutrition and blood supplement tablets, exclusive breastfeeding, MP-ASI, giving Vitamin A, complete basic immunization, PHBS, monitoring babies and toddlers at posyandu and paying attention to fulfilling balanced nutrition for children). By trying to process/utilize local food ingredients with interesting variations so that they attract children's attention to consume them. Keywords: Knowledge, Skills, Nugget Processing, Stunting.